Three characteristic women of Shakespeare - Hoffman, Emmett Vivian (My University, 1898)
Introduction: The study of character, the study of the impulses which prompt humans to dreads includes also a study of one’s own impulses. In interpreting the character of these three great women I can only give to you my idea, my feeling, as to what would prompt me to the same action. I must act as a minor in which these characters are reflected, if my makeup is warped I can only give to you a warped reflection which may be so different from your idea, that it seems absurd. It is not necessary for me to speak of Shakespeare’s life. For that you call him to those who have carefully studied the history as well as the impulses of that great master soul, in whose mind all minds existed, in whose heart every passion existed, each being sovereign for a time.
Citation: Hoffman, Emmett Vivian. Three characteristic women of Shakespeare. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Character; Impulses; Shakespear; Theses; Manuscripts (documents)